2015
DOI: 10.1002/cam4.436
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of implementing molecular‐guided therapy for the treatment of patients with relapsed or refractory neuroblastoma

Abstract: The primary objective of the study was to evaluate the feasibility and safety of a process which would utilize genome-wide expression data from tumor biopsies to support individualized treatment decisions. Current treatment options for recurrent neuroblastoma are limited and ineffective, with a survival rate of <10%. Molecular profiling may provide data which will enable the practitioner to select the most appropriate therapeutic option for individual patients, thus improving outcomes. Sixteen patients with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Pilot studies have demonstrated the feasibility of generating therapeutic treatment plans based on genomic profiling in less than 12 days [137], and a follow-up national, multi-institutional phase I trial showed clinical benefit in 64% of patients (defined as disease stabilization for at least one cycle of therapy or partial response), with an overall response rate of 7% and progression free survival time of 59 days [138]. A subsequent separate single-institution study demonstrated that incorporation of tumor DNA sequencing data into clinical management of patients was feasible, revealed potentially actionable findings in nearly half of patients, and directly led to changes in treatment and family genetic counseling for some patients [139].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…Pilot studies have demonstrated the feasibility of generating therapeutic treatment plans based on genomic profiling in less than 12 days [137], and a follow-up national, multi-institutional phase I trial showed clinical benefit in 64% of patients (defined as disease stabilization for at least one cycle of therapy or partial response), with an overall response rate of 7% and progression free survival time of 59 days [138]. A subsequent separate single-institution study demonstrated that incorporation of tumor DNA sequencing data into clinical management of patients was feasible, revealed potentially actionable findings in nearly half of patients, and directly led to changes in treatment and family genetic counseling for some patients [139].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…The effective chemotherapy regimens for NB primarily include cyclophosphamide, ifosfamide, adriamycin, vincristine, etoposide, and platinum. However, few effective drugs are available for patients who are resistant to front‐line chemotherapy . Paclitaxel (PTX), which is a cytotoxic agent that can bind to the spindle microtubules of tumor cells, causes mitotic arrest and cell death, and has been widely used to treat many adult tumors .…”
mentioning
confidence: 99%
“…Considering this conundrum and the high incidence of recurrence in advanced stages of neuroblastoma (stage III and IV) (4, 6), defining appropriate strategies for treating this cancer particularly in advanced stages is a priority. Presently, we evaluated a broad-spectrum anti-tumor protein MDA-7/IL-24 (11, 12, 16) delivered by a tropism-modified chimeric cancer terminator virus (Ad.5/3- CTV ) (23, 26) in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of tumors at advanced stages combined with the absence of surgical options culminates in very poor patient prognosis. Although some improvements in the overall cure rate of neuroblastomas have been realized using intensive multimodality therapies these therapies promote significant short- and long-term toxicities (1, 3, 4). Only about 2% of neuroblastoma patients with stage III or IV remain disease free with relapse occurring shortly after completing chemotherapy, indicating a negligible effect of these agents long-term (5).…”
Section: Introductionmentioning
confidence: 99%